How does task complexity and task difficulty affect college students’ writing performance? The mediating effect of critical thinking disposition - Yumei Zou; Florence Kuek; Xiaoli Cheng; Wenqin Feng (PLoS ONE, 2025)
This study investigated the effects of task complexity, task difficulty, and critical thinking disposition on college students’ writing performance. 201 participants were selected via probability sampling. Each completed three writing tasks of varying complexity, resulting in a corpus of 603 compositions. A follow-up questionnaire assessed task difficulty and critical thinking disposition. Results showed that both task complexity and difficulty significantly affected writing performance. Specifically, four sub-constructs of critical thinking disposition (analyticity, systematicity, inquisitiveness, and cognitive maturity) were positively associated with writing performance and mediated the relationship between task difficulty and writing performance. Structural and mediation models were established using Smart PLS to illustrate these relationships. This study contributes to the growing field of cognitive-oriented and affective-related research by exploring the cognitive and affective factors influencing writing and provides practical recommendations for writing assessment and pedagogy.